2022
DOI: 10.3390/medicina58070883
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sleep and Work Productivity among White-Collar Workers during the COVID-19 Pandemic

Abstract: Background and Objectives: The COVID-19 pandemic has disrupted routine sleep and work patterns in the general population. We conducted an anonymous online survey among white-collar workers from various finance, IT and technology companies in Lithuania to define factors associated with worse sleep quality and diminished productivity during a COVID-19 lockdown. Materials and Methods: Employees of selected companies in Lithuania completed an anonymous questionnaire online that included the Pittsburgh Sleep Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The prevalence of poor sleep quality among the working adults during the MCO period of COVID-19 pandemic in Malaysia is 59.4%, which is found to be high. The high prevalence was also seen in the studies done by Abbas et al ( 2021 ), Kantor et al ( 2022 ) and Žilinskas et al ( 2022 ), which are 78.8%, 68.9% and 43%, respectively. However, in a study from China by Yang et al ( 2020 ), the prevalence was lower, 14.9%.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The prevalence of poor sleep quality among the working adults during the MCO period of COVID-19 pandemic in Malaysia is 59.4%, which is found to be high. The high prevalence was also seen in the studies done by Abbas et al ( 2021 ), Kantor et al ( 2022 ) and Žilinskas et al ( 2022 ), which are 78.8%, 68.9% and 43%, respectively. However, in a study from China by Yang et al ( 2020 ), the prevalence was lower, 14.9%.…”
Section: Discussionsupporting
confidence: 61%
“…During the lockdown period of the COVID-19 pandemic, many studies have been conducted by researchers worldwide to measure the sleep quality of different populations (Tasnim et al, 2020 ). A study by Žilinskas et al ( 2022 ) found that 43% of white-collar workers had poor sleep quality during the lockdown period, 68.9% of participants from general population had poor sleep quality in the study done in United Kingdom (Kantor et al, 2022 ), 14.9% of the employees who returned to work in China after the lockdown (Yang et al, 2020 ) had poor sleep quality during the initial period of pandemic and as high as 78.8% among healthcare workers from Kuwait in a study done by Abbas et al ( 2021 ). Studies exploring sleep quality in Malaysia have focused on university students and healthcare workers (Hazizul Hasan and AE Moustafa, 2022 ), whereas others have elaborated extensively on the psychological impacts of the pandemic on the working population (Abdul Latif et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Four studies had been conducted in Japan ( 31–34 ) and 4 in United Kingdom ( 35–38 ), 3 in United States ( 39–41 ), 2 in China ( 42 , 43 ), Germany ( 44 , 45 ), and the Republic of Korea ( 46 , 47 ), and 1 in Sweden ( 16 ), Wales ( 48 ), Canada ( 22 ), Turkey ( 49 ), Lithuania ( 50 ), Portugal ( 51 ), Australia and New Zealand ( 52 ), and Belgium and the Netherlands ( 53 ). In 14 of the 25 selected articles, collection took place in 2020; 6 of the 25 were collected in 2021; and the remaining 5 were collected over months in both 2020 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that between 70.6% ( 43 ) and 26% ( 38 ) of the subjects in the included studies showed sickness presenteeism. In addition, a number of factors may have also favoured presenteeism or sickness presenteeism, such as mental health-related factors [burnout ( 34 , 45 , 49 , 51 ), stress ( 33–35 , 38 , 42 , 44 , 45 , 47 , 49 ), depression ( 46 ), fear of COVID-19 ( 49 ), no well-being ( 16 , 40 ), cyberbullying ( 51 ), sleep disturbance ( 34 ), concern about having enough food ( 41 ), social isolation ( 38 ), and no resilience ( 38 )]; individual factors [poor marital relationship ( 31 ), health status ( 42 ), being young ( 38 ), attention-deficit/hyperactivity disorder symptoms ( 32 ), workers who experienced interrupted medical care ( 33 , 40 ), low physical activity ( 38 , 50 ), sedentary behaviours ( 52 ), having children ( 41 ), having health insurance ( 41 ), and having a chronic illness ( 38 )]; factors related to the situation caused by COVID-19 [confinement ( 45 ), having symptoms of respiratory infectious disease ( 48 ), not volunteering to work on the frontline ( 47 ), impact on business operations, loss of contract, and risk of bankruptcy ( 16 )]; and factors arising from working conditions [perceived organisational support ( 49 ), direct patient care ( 39 ), work functioning or task performance impairment ( 31 , 42 , 43 , 53 ), work fatigue ( 34 , 43 ), safety climate ( 22 ), workload ( 22 ), having no one to replace them ( 48 ), geographical distribution ( 48 ), transition from in-person to online modes of working ( …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation